Cardiac sarcoidosis: a comprehensive review of risk factors, pathogenesis, diagnosis, clinical manifestations, and treatment strategies - Shah, Hussain Haider; Zehra, Syeda Alishah; Shahrukh, Aliza; Waseem, Radeyah; Hussain, Tooba; Hussain, Muhammad Sheheryar; Batool, Fareeha; Jaffer, Muhammad (Frontiers in Cardiovascular Medicine, 2023)
Cardiac Sarcoidosis (CS) is a deadly consequence of systemic sarcoidosis that inflames all three layers of the heart, especially the myocardium—clinical signs of CS range from asymptomatic disease to abrupt cardiac death. CS generally remains undiagnosed secondary to a lack of definitive diagnostic criteria, a high percentage of false negative results on endomyocardial biopsy, and ill-defining clinical manifestations of the disease. Consequently, there is a lack of evidence-based recommendations for CS, and the present diagnostic and therapeutic management depend on expert opinion. The aetiology, risk factors, clinical symptoms, diagnosis, and therapy of CS will be covered in this review. A particular emphasis will be placed on enhanced cardiovascular imaging and early identification of CS. We review the emerging evidence regarding the use of Electrocardiograms (ECGs), Magnetic Resonance Imaging (MRI), and Positron Emission Tomography (PET) imaging of the heart to identify and quantify the extent of myocardial inflammation, as well as to guide the use of immunotherapy and other treatment regimens, such as ablation therapy, device therapy, and heart transplantation, to improve patient outcomes.